Wiener-Hopf optimal control of a hydraulic canal prototype with fractional order dynamics. (November 2018) - Feliu-Batlle, Vicente; Feliu-Talegón, Daniel; San-Millan, Andres; Rivas-Pérez, Raúl
Abstract: This article addresses the control of a laboratory hydraulic canal prototype that has fractional order dynamics and a time delay. Controlling this prototype is relevant since its dynamics closely resembles the dynamics of real main irrigation canals. Moreover, the dynamics of hydraulic canals vary largely when the operation regime changes since they are strongly nonlinear systems. All this makes difficult to design adequate controllers. The controller proposed in this article looks for a good time response to step commands. The design criterium for this controller is minimizing the integral performance index ISE . Then a new methodology to control fractional order processes with a time delay, based on the Wiener-Hopf control and the Padé approximation of the time delay, is developed. Moreover, in order to improve the robustness of the control system, a gain scheduling fractional order controller is proposed. Experiments show the adequate performance of the proposed controller. Highlights: New results on the application of control of a laboratory hydraulic canal prototype that has fractional order dynamics. Extension of the Wiener-Hopf design method to the case of fractional order processes with time delay. Propose of a gain scheduling fractional order controller based on the controller previously designed. Experimental validation and robustness analysis of the proposed controller.